GPS detection of ionospheric Rayleigh wave and its source following the 2012 Haida Gwaii earthquake. Issue 1 (30th January 2017) - Jin, Shuanggen; Jin, Rui; Li, D.
Abstract: The processes and sources of seismo‐ionospheric disturbances are still not clear. In this paper, coseismic ionospheric disturbances (CIDs) are investigated by dual‐frequency GPS observations following the Mw = 7.8 earthquake as results of the oblique‐thrust fault in the Haida Gwaii region, Canada, on 28 October 2012. Results show that the CIDs with an amplitude of up to 0.15 total electron content units (TECU) are found with spreading out at 2.20 km/s, which agree well with the Rayleigh wave propagation speed at 2.22 km/s detected by the bottom pressure records at about 10 min after the onset. The CIDs are a result of the upward propagation acoustic waves trigged by the Rayleigh wave in sequence from near field to far field. The strong correlation is found between the CIDs and the vertical ground motion recorded by seismometers nearby the epicenter. The total electron content (TEC) series from lower‐elevation angle GPS observations have higher perturbation amplitudes. Furthermore, the simulated ionospheric disturbance following a vertical Gauss pulse on the ground based on the finite difference time domain method confirms the ionospheric Rayleigh wave signature in the near field and the vertical ground motion dependence theoretically. The vertical ground motion is the dominant source of the ionospheric Rayleigh wave and affects the CID waveform directly. Key Points: Ionospheric Rayleigh waves are detected by GPS and agree well with BPR measurements A strong correlation is found between ionospheric Rayleigh waves and vertical ground motions The vertical ground motion is the dominated source of ionospheric Rayleigh waves